Preservation of High-Moisture Sorghum Silage Using Combination of Biological and Chemical Additives in the Tropical Region - Ardiansyah, M.; Fitriani, D.; Noviandi, C. T.; Kurniawati, A.; Paradhipta, D. H. V. (Tropical Animal Science Journal, 2025)
This study aimed to investigate the effect of the biological and chemical additives on fermentation characteristics, aerobic stability, and ruminal digestibility of high-moisture sorghum silage. A mixture of Lactiplantibacillus plantarum FNCC 0020 (LP) and Limosilactobacillus fermentum BN21 (LF) was used as a biological additive and potassium sorbate as a chemical additive. At the milk ripening stage (26.8% of DM), sorghum was harvested, chopped to 3-5 cm length, and ensiled into 20 L silo (5 kg) for 100 days. Subsequently, various additives were added, including a control group without additives (CON), LF + LP with a ratio of 1:1 at 1 x 105 cfu/g fresh weight (INO), potassium sorbate at 1 g/kg fresh weight (PS), and INO + PS (MIX). Each treatment used 5 silos as replication. The results showed that INO silage had the lowest (p<0.05) pH with the highest (p<0.05) contents of lactate and acetate, as well as lactic acid bacteria (LAB) count. PS silage produced the minimum contents of lactate and acetate but had lower yeast compared to CON silage. MIX silage had lower (p<0.05) lactate and acetate contents than CON silage, with a similar effect on yeast inhibition to PS silage. Furthermore, PS and MIX silages had higher (p<0.05) aerobic stability and in vitro digestibility of dry matter and organic matter than CON and INO. These results showed that combining biological and chemical additives was more effective in improving fermentation, aerobic stability, and ruminal digestibility of high-moisture sorghum silage.